Single-institution cross-sectional study to evaluate need for information and need for referral to psychooncology care in association with depression in brain tumor patients and their family caregivers - Christiane Reinert; Michael Gerken; Katharina Rathberger; Katharina Krueger; Monika Klinkhammer-Schalke; Patricia Lindberg-Scharf; Oliver Koelbl; Martin A. Proescholdt; Markus J. Riemenschneider; Tobias Pukrop; Elisabeth Bumes; Markus Hutterer; et al. (BMC Psychology, 2020)
Abstract Background The prognosis of patients with brain tumors is widely varying. Psychooncologic need and depression are high among these patients and their family caregivers. However, the need for counselling and need for referral to psychooncology care is often underestimated. Methods We performed a single-institution cross-sectional study to evaluate psychooncologic need, depression and information need in both patients and their family caregivers. The Hornheider Screening Instrument (HSI) and the Patient Health Questionnaire (PHQ-9) were used to evaluate psychooncologic need and depression, and a study-specific questionnaire was developed to evaluate information need. Multivariable analyses were performed to detect correlations. Results A total of 444 patients and their family caregivers were approached to participate, with a survey completion rate of 35.4%. More than half of the patients and family caregivers were in need for referral to psychooncology care and 31.9% of patients suffered from clinically relevant depression. In multivariable analysis, psychooncologic need were positively associated with mild (odds ratio, OR, 7.077; 95% confidence interval, CI, 2.263–22.137; p = 0.001) or moderate to severe (OR 149.27, 95% CI 26.690–737.20; p <  0.001) depression. Patient information need was associated with depression (OR 3.007, 95% CI 1.175–7.695; p = 0.022). Conclusions Unmet counselling need in brain tumor patients and their family caregivers associate to high psychooncologic need and depression. Adequate information may decrease the need for referral to psychooncology care and treatment of depression in these patients. Future studies should further explore these relations to promote development of supportive structures.